2012
DOI: 10.1155/2012/929052
|View full text |Cite
|
Sign up to set email alerts
|

The PPAR Gamma Agonist Troglitazone Regulates Erk 1/2 Phosphorylation via a PPARγ-Independent, MEK-Dependent Pathway in Human Prostate Cancer Cells

Abstract: Thiazolidinediones (TZDs) dramatically reduce the growth of human prostate cancer cells in vitro and in vivo. To determine whether the antitumor effects of TZDs were due in part to changes in the MEK/Erk signaling pathway, we examined the regulation of Erk phosphorylation by the TZD troglitazone within the PC-3 and C4-2 human prostate cancer cell lines. Western blot analysis revealed troglitazone-induced phosphorylation of Erk in both PC-3 and C4-2 cells. Troglitazone-induced increases in Erk phosphorylation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…Paradoxically, it appears that PPARG activation using synthetic ligands (at high concentrations) suppresses in vitro growth in LNCaP, DU145, and PC3 prostate cancer cell lines and in vivo s.c. PC3 growth (20,24,25). However, recent evidence suggests these agonists may act via a PPARGindependent manner to induce cell cycle arrest and apoptosis in CaP (24).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, it appears that PPARG activation using synthetic ligands (at high concentrations) suppresses in vitro growth in LNCaP, DU145, and PC3 prostate cancer cell lines and in vivo s.c. PC3 growth (20,24,25). However, recent evidence suggests these agonists may act via a PPARGindependent manner to induce cell cycle arrest and apoptosis in CaP (24).…”
Section: Discussionmentioning
confidence: 99%
“…Though the roles of PPARγ in cancer therapy are debatable, accumulating evidence suggested that activation of PPARγ by agonists exerts an inhibitory effect on cancer cells [32]. For example, PPARγ agonists dramatically reduced cell growth of hepatocellular carcinoma [33], prostate cancer [34], and gastric cancer [35] via regulating the expression and blocking the oncogenic proteins. In our study, we found that PPARγ agonist RGZ had an ability to inhibit proliferation of esophageal cancer cells in time- and dose-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
“…However, this alternative mechanism of action also appears unlikely based on a prior study demonstrating decreased MUC1 expression following treatment of epithelial cells with antioxidants (29). Finally, phosphorylation of ERK1/2 through the TNF-␣ receptor is known to activate MUC1 expression (25,29), and Bolden et al (8) recently demonstrated that treatment of human prostate cancer cells with TGN induced ERK1/2 phosphorylation via a PPAR␥-independent pathway. However, this effect was only observed at relatively high TGN concentrations (40 M) and no effect on ERK1/2 activation was seen at the doses used in the present study (Ͻ 1.0 M).…”
Section: ϫ/ϫ (Iii Iv) Mice Following Inoculation With Pbs Vehicle Comentioning
confidence: 99%